Comparative study on the in vitro replication and genomic variability of Argentinean field isolates of bovine herpesvirus type 4 (BoHV-4) - Verna, Andrea Elizabeth; Perez, Sandra; Manrique, Julieta Marina; Leunda, Maria Rosa; Odeon, Anselmo Carlos; Jones, Leandro Roberto (2017)
Bovine herpesvirus 4 (BoHV-4) is a gammaherpesvirus, belonging to the Rhadinovirus genus, which is increasingly associated with various problems of the reproductive tract of cattle. In Argentina, analysis of BoHV-4 strains isolated from cervico-vaginal mucus of aborted cows revealed a high genetic divergence among strains, which could be classified in three different groups: Genotype 1 comprises Movar-like strains (European prototype), Genotype 2 includes DN599 like strains (American prototype) and Genotype 3 corresponds to a novel genotype group. Understanding the replication behavior in cell cultures and the molecular characteristics of this pathogen of cattle is critical for the rational design of in vitro experiments. The aim of this work was to quantitatively evaluate the replication properties of different Argentinean BoHV-4 strains and to characterize their phylogenetic relationships. Significant differences were evident among the virus titers of the different BoHV-4 isolates in vitro. The most conserved gene was the major capsid protein (ORF25). The glycoprotein B (gB), glycoprotein H (gH), and thymidine kinsase (TK) genes displayed both synonymous and nonsynonymous substitutions, with the highest diversity observed for gB, which displayed amino acid substitutions in 24 out of the 178 positions examined. Strains 09/759, 12/512, and 07/568 presented a deletion encompassing amino acid position 27 to 35, whereas strains 07/435 and 09/227 had a deletion from position 28 to 35. Two strains, 07/435 and 09/227, also displayed the highest divergence compared to the other strains analyzed. This study provides information about the in vitro replication and behavior of nine field isolates of BoHV-4. These findings are relevant since available information on the in vitro growth characteristics of BoHV-4 strains is scarce. The results from this study may also be useful for establishing comparisons with other related viruses.